RELATIONSHIP OF SELF-COMPASSION AND EMPATHY IN FINAL YEAR GUIDANCE AND COUNSELING STUDENTS - Aliva Karina Muyassar; Happy Karlina Marjo; Eka Wahyuni (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to see an overview of the relationship between the level  of self-compassion and empathy in final year students at the State University of Jakarta (UNJ) and Sultan Ageng Tirtayasa University (UNTIRTA), and relate it to the urgency of the role of Guidance and Counseling services in universities. The approach used was quantitative descriptive, with a sampling technique using convenience sampling techniques for the number of respondents as many as 110 students (55 from UNJ and 55 from UNTIRTA). This study aims to get an overview and relationship  of self-compassion and empathy in final year BK students. The instruments used are the Self-Compassion Scale (SCS) and the Empathy Assessment Scale (EAS). The results showed that the average self-compassion score  in UNJ and UNTIRTA students was 75.64, with a standard deviation of 7.069, which shows a relatively good and stable level of self-concept in both universities. However, there is a striking difference in the level of empathy. UNJ students have an average EAS score of 76.07 with a wide range (36–87), while UNTIRTA students have a lower average EAS score, which is 56.53, with a narrower range (46–61). As many as 86% of students are in the category of moderate empathy, 9% low, and only 5% have high empathy. These findings suggest that although final year students have a fairly good level of self-acceptance, empathic abilities have not been optimally developed. This has important implications for guidance and counseling services, namely the need to prepare intervention programs that are directed at strengthening emotional awareness and empathy through individual, group, and social-emotional counseling.